2020
DOI: 10.1186/s43055-020-00252-9
|View full text |Cite
|
Sign up to set email alerts
|

Current imaging techniques for evaluation of fistula in ano: a review

Abstract: Background: Fistula in ano is one of the common anorectal disorders which have a tendency to recur specially in complex cases usually due to missed or undetected sepsis at the time of examination or surgery. A correct identification of the primary source of crypt infection along with a complete understanding of the anatomical course of primary and secondary tracks and abscesses is a prerequisite for the successful management of fistula. Preoperative evaluation of fistula in ano using radio-imaging techniques p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
(104 reference statements)
1
16
0
1
Order By: Relevance
“…Our study showed that MRI was superior to ultrasound in the detection of the fibrotic tracts which agreed with Sharma et al study [15].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that MRI was superior to ultrasound in the detection of the fibrotic tracts which agreed with Sharma et al study [15].…”
Section: Discussionsupporting
confidence: 93%
“…TRUS had minimal use in our patients studied despite the method is easily performed (available in most anal surgery departments); the method to date is overlapped by MRI findings; in our patients was performed only in few cases, when the MRI findings were inconclusive for the level of the internal opening of AF. [19,20] According to the transverse anal line all fistulas were classified as anterior or posterior anal fistulas. The real classification regarding the characteristics of fistula as length, route, complexity and participation of anal sphincter system in the formation of AF was based in MRI findings.…”
Section: Methodsmentioning
confidence: 99%
“…Perianal fistula is a condition in which a fistulous communication between the skin and the anorectum develops in the perianal region [1]. Perianal fistulas affect 8.6 cases per 100,000 people [2], with males being more affected than females [3], particularly those in their 40s.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional fistulograms have been used as an imaging method for perianal fistula before the introduction of magnetic resonance imaging (MRI) [3]. The conventional fistulogram involves injecting contrast media into the external skin opening of the fistulous tract and then deter-mining the extent of the fistulous tract using fluoroscopic imaging [1]. The inability to locate internal anal openings, secondary tracts, and abscesses, as well as the patient's pain and discomfort during the procedure, are the main drawbacks of a conventional fistulogram [1].…”
Section: Introductionmentioning
confidence: 99%